In vitro allelopathy of the aqueous extract of Calathea lutea on the initial growth of Lactuca sativa L - Ramírez Castro, Kriss Emelyn (2022)
To determine the in vitro allelopathic effect of the aqueous extract of Calathea lutea (Aubl.) E.Mey. ex Schult. (bijao) on the initial growth of Lactuca sativa L. (lettuce) variety White Boston. An extract at 15% w/v was prepared with each part of the bijao plant (stem, leaf, and root), it was left to stand for 48 hours, then extracts at 2, 4, 6% concentrations were obtained by dilution. 10 lettuce seeds/petri dishes were sown, irrigating daily with 5 ml of each concentration of the extract. The control treatment received distilled water. The research was adjusted to a Complete Random Design (DCA), with a 3A x 4B factorial arrangement (A = parts of the plant and B = concentration of the extract), with four repetitions. At 10 days after germination, it was statistically evaluated and demonstrated (p ≤ 0.05) that the germination percentage (7.5%), root length (1.23 cm), stem fresh weight (0.0085 g), dry weight of the stem (0.0012 g), fresh weight of the radicle (0.0010 g), and dry weight of the radicle (0.0005 g), were significant in the interaction of leaf extract at 6 % concentration. It is concluded that the aqueous extract of leaf of Calathea lutea showed an allelopathic effect as the concentration increased, on the initial growth parameters in lettuce seedlings.